PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN KOSUMEN PADA GONG CAFE DALUNG - I Nyoman Bayu Oka Nuratma (STIE BIITM, 2019)
ABSTRACT The title of the research is the Effect of Service Quality and Price on Consumer Satisfaction at Gong Cafe Dalung. The types of service quality and prices are very diverse, business people are required to create the right strategy. If consumers feel satisfied with the services provided, it will create satisfaction with consumers. The purpose of this study was to determine the effect of service quality and price on consumer satisfaction at Gong Cafe Dalung. The sample from this study was 60 guests at Gong Cafe Dalung. The data source used is premier and secondary data. Data were analyzed using a computer program SPSS for Windows ver 22. Methods of data collection in this study using interview techniques, with a questionnaire using a Likert scale. The data analysis technique uses multiple linear regression analysis. The results of the study were obtained from the results of statistical analysis showing that partially the service quality variable (X1) had a positive and significant effect on the t-test results of 8.927 and sig 0,000 for the variable customer satisfaction (Y) and price variables (X2). t-test results of 1.672 with sig 0.727 on consumer satisfaction (Y) at Gong Cafe Dalung, while simultaneously showing that the magnitude of the influence of service quality and prices on consumer satisfaction at Gong Cafe Dalung is 42.901 and sig 0.000 by testing hypotheses using f-test , with the result that the variable quality of service (X1) and price (X2) on customer satisfaction (Y) has a positive and significant effect on Gong Cafe Dalung.